Association between Testosterone/Estradiol Ratio and Risk of Cardiometabolic Diseases in Women at Menopause Transition Age - Fabrice Boris Awadji; Bi Huang; Bryan Richard Sasmita; Samuel Chigbo Obiegbusi; Armin Czika; Yuzhou Xue; Suxin Luo; Alphonse Sowanou; Gang Liu (IMR Press, 2022)
Background: Imbalance of testosterone/estradiol ratio are frequently reported to be associated with the risk of cardiometabolic diseases; however, studies have yet to report the testosterone/estradiol ratio and its relationship to cardiometabolic diseases in women at menopause transition. This study aimed to explore the association between testosterone/estradiol ratio with cardiometabolic diseases in women during their menopausal transition age. Methods: 551 women aged from 45 to 55 years old were involved in this study. Their baseline information, disease comorbidity, blood biochemical tests, echocardiography and serum sex hormones were collected. Women were categorized by tertile distribution of testosterone/estradiol ratio. We used binary logistic regression model (for odds ratio) and poissoon loglinear model (for prevalence ratio) to evaluate the association between testosterone/estradiol ratio with cardiometabolic diseases. Results: The mean age of the study population was 48.6 ± 3.5 years old. Taking testosterone/estradiol ratio <3.9 as reference, the odds ratio with 95% confidence interval across the tertile groups for obesity were: 1.0 (reference), 2.32 (0.96-5.64), 4.70 (1.75-12.67) (p for trend = 0.002); for hypertension were: 1.0 (reference), 2.37 (1.45-3.86), 2.02 (1.12-3.62) (p for trend = 0.013); for cardiometabolic diseases were: 1.0 (reference), 2.29 (1.47-3.56), 2.34 (1.37-3.99) (p for trend = 0.013), compared with the prevalence ratio of 1.0 (reference), 1.64 (1.26-2.15), 1.65 (1.21-2.23) (p for trend = 0.001), respectively. Conclusions: Higher testosterone/estradiol ratio was associated with elevated prevalence of cardiometabolic diseases in women at menopause transition period.